A surface-engineered tape-casting fabrication technique toward the commercialisation of freestanding carbon nanotube sheets. Issue 36 (31st August 2017) - Susantyoko, Rahmat Agung; Karam, Zainab; Alkhoori, Sara; Mustafa, Ibrahim; Wu, Chieh-Han; Almheiri, Saif
Abstract : Surface-engineered tape-casting (SETC) is a facile and scalable preparation method to fabricate freestanding, flexible and foldable MWCNT and MWCNT-composite sheets. Abstract : Various applications of freestanding multi-walled carbon nanotube (MWCNT) sheets (also known as buckypapers), although very promising in the laboratory, failed to meet the technology readiness level for commercialisation due to the use of non-scalable fabrication methods. Herein, we developed a surface-engineered tape-casting (SETC) technique which is a facile and scalable preparation method to fabricate freestanding, flexible and foldable buckypapers using tape-casting on a surface-engineered conveyor-belt without a mould. The SETC technique has several advantages: it can be implemented in both batch and roll-to-roll processing; has a high throughput; produces a large area with tuneable length, thickness, density and composition; and produces sheets from any commercially available carbon nanotubes with superior properties. The SETC technique solves the main challenge of tape-casting which is the separation of the dried MWCNT sheet from the supporting-substrate. This challenge originates from the fact that MWCNTs always tend to stick to the substrate which makes it almost impossible to peel as a perfect sheet. We found out that easy peeling of the buckypaper from a substrate can be achieved if the following conditions are satisfied: (a) enough difference between MWCNTs and substrate surface energies and (b) the micro-pyramid pore structure of the substrate morphology. Moreover, the SETC technique was able to preserve the MWCNT alignment within the sheet. We demonstrated the application of a SETC-made MWCNT–LiFePO4 buckypaper composite in lithium-ion batteries with an excellent specific capacity of 86.79 mA h gLiFePO4 −1 (61.20 mA h gMWCNT+LiFePO4 −1 ) at a high discharge rate of 1905 mA gLiFePO4 −1 (1270 mA gMWCNT+LiFePO4 −1 ) for 1000 cycles.